Yorktown Victory Center Museum Teacher Resource Packet - Jamestown-Yorktown Foundation, Williamsburg, VA. Education Dept.; Jamestown-Yorktown Foundation, Williamsburg, VA. Education Dept. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This resource packet provides information and activities for teaching abut the historical significance of Yorktown, Virginia in the American Revolution. Teachers' materials include brief background essays on: (1) "Summary of the American Revolution in Virginia"; (2) "Life in the Army"; (3) "Life in Revolutionary Virginia"; (4) "African-Americans in Early Virginia"; and (5) "The Town of York." Classroom activities include colonial games, food preparation, vocabulary study, writing suggestions, and music study. Contains a suggested reading list. (EH)
Availability: Education Department, Jamestown-Yorktown Foundation, P.O. Drawer JF, Williamsburg, VA 23185.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Colonial History (United States); Elementary Secondary Education; Heritage Education; Local History; Revolutionary War (United States); Social Studies; State History; United States History; Virginia (Yorktown); Guides, Classroom -- Teacher